The Mediterranean Sea heat and mass budgets: Estimates, uncertainties and perspectives. (August 2017) - Jordà, G.; Von Schuckmann, K.; Josey, S.A.; Caniaux, G.; García-Lafuente, J.; Sammartino, S.; Özsoy, E.; Polcher, J.; Notarstefano, G.; Poulain, P.-M.; Adloff, F.; Salat, J.; et al.
Highlights: A review of the existing knowledge on the Mediterranean Sea heat and mass budgets is presented. An update of the estimates of the different components of the budgets is included. Perspectives and recommendations for future improvements are listed. Abstract: This paper presents a review of the state-of-the-art in understanding and quantification of the Mediterranean heat and mass (i.e. salt and water) budgets. The budgets are decomposed into a basin averaged surface component, lateral boundary components (through the Gibraltar and the Dardanelles Straits), a river input component and a content change component. An assessment of the different methods and observational products that have been used to quantify each of these components is presented. The values for the long term average of each component are also updated based on existing literature and a first estimate of heat fluxes associated with the riverine input has been produced. Special emphasis is put on the characterization of associated uncertainties and proposals for advancing current knowledge are presented for each budget component. With the present knowledge of the different components, the Mediterranean budgets can be closed within the range of uncertainty. However, the uncertainty range remains relatively high for several terms, particularly the basin averaged surface heat fluxes. Consequently, the basin averaged heat budget remains more strongly constrained by the Strait of Gibraltar heat transport than by the surface heat flux. It is worth remarking that if a short (∼few years) averaging period is used, then the heat content change must also be considered to constrain the heat budget. Concerning the water and salt fluxes, the highest uncertainties are found in the direct estimates of the Strait of Gibraltar water and salt transport. Therefore, the indirect estimate of those transports using the budget closure leads to smaller uncertainties than the estimates based on direct observations. Finally, estimates of Mediterranean heat and salt content trends are also reviewed. However, these cannot be improved through the indirect estimates due to the large temporal uncertainties associated to the surface fluxes and the fluxes through Gibraltar. The consequences of these results for estimates of the Mediterranean temperature and salinity trends obtained from numerical modelling are also considered.